Game Edukasi Mengenal Mata Uang Indonesia “Rupiah” Untuk Pengetahuan Dasar Anak-Anak Berbasis Android - Topan Hadi; Nana Suarna; Ade Irma Purnamasari; Odi Nurdiawan; Saeful Anwar (STMIK Budi Darma, 2021)
In the current digital era, technology and science are growing rapidly to penetrate various aspects of life, including in the field of education. By utilizing the provision of applications that contain elements of education, it gives birth to new ways in one's learning process, so that the learning process is more interesting and efficient. However, there is no learning about Indonesian currency, making the children reluctant to learn. They only know about the nominal currency, without knowing in detail the elements that exist in Indonesian currency. From these problems, a conclusion was drawn to get a solution by making an educational game in the form of introducing Indonesian paper currency on Android as a learning medium for children SDN 3 Kasdul Depok Sidapurna Cirebon). Making educational games on Android can be easily, effectively. The development of this game uses the ADDIE (Analysis, Design, Development, Implementation, Evaluation) method. The research was conducted using a quantitative concept, where the data were taken based on a questionnaire and processed by statistical figures. The results of this study showed that the interest (0.046) & motivation (0.001) variable was said to be < 0.05 so that it affected the currency recognition game